Pengaruh Disiplin Kerja dan Job Insecurity Terhadap Kinerja Karyawan PT Bhakti Sari Perkasa Bersama - Sahara Sahara (Value : Jurnal Manajemen dan Akuntansi, 2021)
The purpose of this research is to analyze the relationship between Work Discipline and Job Insecurity variables on performance. The research method used in this research is quantitative research method. The population in this study were employees of PT. Bhakti Sari Husada Bersama, Cirebon totaling 84 people. The sampling technique in this study used stratified techniques totaling 84 respondents. Data collection techniques used by using questionnaires and interviews. The measurement scale of the instrument used in this study uses the Likert scale. The data analysis technique used is multiple linear regression analysis. The results showed that there was a positive and significant influence both partially and simultaneously between the variables of Work Discipline and Job Insecurity on employee performance. Keywords: Disiplin kerja; Job Insecurity; Kinerja Karyawan